Bone Tumor Environment as a Potential Therapeutic Target in Ewing Sarcoma - Redini, Françoise; Heymann, Dominique (Frontiers in Oncology, 2015)
Ewing sarcoma is the second most common pediatric bone tumor, with three cases per million worldwide. In clinical terms, ES is an aggressive, rapidly fatal malignancy that mainly develops in osseous sites (85%), but also in extraskeletal soft tissue. It spreads naturally to the lungs, bones and bone marrow with poor prognosis in the two latter cases. Bone lesions from primary or secondary (metastases) tumors are characterized by extensive bone remodeling, more often due to osteolysis. Osteoclast activation and subsequent bone resorption is responsible for the clinical features of bone tumors including pain, vertebral collapse and spinal cord compression. Based on the “vicious cycle” concept of tumor cells and bone resorbing cells, drugs which target osteoclasts may be promising agents as adjuvant setting for treating bone tumors, including Ewing sarcoma. There is also increasing evidence that cellular and molecular protagonists present in the bone microenvironment play a part in establishing a favorable “niche” for tumor initiation and progression. The purpose of this review is to discuss the potential therapeutic value of drugs targeting the bone tumor microenvironment in Ewing Sarcoma. The first part of the review will focus on targeting the bone resorbing function of osteoclasts by means of bisphosphonates (BPs) or drugs blocking the pro-resorbing cytokine Receptor Activator of NF-kappa B Ligand (RANKL). Second, the role of this peculiar hypoxic microenvironment will be discussed in the context of resistance to chemotherapy, escape from the immune system, or neo-angiogenesis. Therapeutic interventions based on these specificities could be then proposed in the context of Ewing sarcoma.